Benny Uncovers a Mystery : The Boxcar Children #19 - Warner, Gertrude Chandler, 1890-1979; Cunningham, David, 1938- (Chicago : A. Whitman, 1976)
Two brothers take summer jobs at a department store where a series of peculiar events brings them under suspicion.
Accelerated Reader
Keywords: Boxcar children (Fictitious characters) -- Juvenile fiction; Orphans -- Juvenile fiction; Families -- Juvenile fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Department stores -- Fiction; Mystery and detective stories; Detective and mystery stories; Detective fiction; Mystery fiction